2009
DOI: 10.1136/ard.2009.111294
|View full text |Cite
|
Sign up to set email alerts
|

PADI4 genotype is not associated with rheumatoid arthritis in a large UK Caucasian population

Abstract: BackgroundPolymorphisms of the peptidylarginine deiminase type 4 (PADI4) gene confer susceptibility to rheumatoid arthritis (RA) in East Asian people. However, studies in European populations have produced conflicting results. This study explored the association of the PADI4 genotype with RA in a large UK Caucasian population.MethodsThe PADI4_94 (rs2240340) single nucleotide polymorphism (SNP) was directly genotyped in a cohort of unrelated UK Caucasian patients with RA (n=3732) and population controls (n=3039… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 27 publications
0
48
3
2
Order By: Relevance
“…This result is supported by a recent meta-analysis which confirmed a lack of association between PADI4_94 genotype and RA in people of European descent (OR = 1.1, 95% CI: 1.0-1.1; P = 0.12). 71 This meta-analysis contrasted two earlier meta-analyses which suggested that the PADI4_94 polymorphism confers susceptibility to RA in those of European descent (OR = 1.1; 95% CI: 1.0-1.2; P = 0.0096), albeit to a lesser degree than in Asian subjects. 72,73 The discrepancy between studies of Caucasian descent can be explained, at least in part, by previous studies being underpowered to detect an OR of this level, thus producing false-positive results.…”
Section: Padi4 Is Associated With Ra Pathogenesiscontrasting
confidence: 68%
“…This result is supported by a recent meta-analysis which confirmed a lack of association between PADI4_94 genotype and RA in people of European descent (OR = 1.1, 95% CI: 1.0-1.1; P = 0.12). 71 This meta-analysis contrasted two earlier meta-analyses which suggested that the PADI4_94 polymorphism confers susceptibility to RA in those of European descent (OR = 1.1; 95% CI: 1.0-1.2; P = 0.0096), albeit to a lesser degree than in Asian subjects. 72,73 The discrepancy between studies of Caucasian descent can be explained, at least in part, by previous studies being underpowered to detect an OR of this level, thus producing false-positive results.…”
Section: Padi4 Is Associated With Ra Pathogenesiscontrasting
confidence: 68%
“…[15][16][17] Examples are a PTPN22-R620W polymorphism which is strongly associated with RA and other autoimmune diseases in Caucasian populations, but is absent in Orientals, and an association with PADI4 SNP found in Japanese populations which is not detected in most Caucasian populations, despite the presence of these gene polymorphisms. [15][16][17][18][19][20] Our own studies of the Cree/Ojibway population in Central Canada have suggested a 2-3% prevalence rate of diagnosed RA, and a 60-70% frequency of SE alleles in the background population. 7,8,21 We sought to determine additional non-HLA genes that may contribute to the high frequency of RA detected in this population.…”
Section: Introductionmentioning
confidence: 96%
“…The R620W variant of the PTPN22 gene is strongly and consistently associated with RA in Europeans (10,11) but not in Asians or black South Africans (12)(13)(14). In contrast, specific haplotypes of the PADI4 gene confer risk for RA in Asians (15)(16)(17)(18) and less or no risk in Europeans (9,(18)(19)(20)(21). However a haplotype in the STAT4 gene is associated with RA in both Europeans and Asians (22,23).…”
Section: Introductionmentioning
confidence: 99%